Hypersensitivity reaction with intravenous GnRH after pulsatile subcutaneous GnRH treatment in male hypogonadotrophic hypogonadism. Issue 749 (March 1988) - Popović, V.; Milosević, Z.; Djukanović, R.; Micić, D.; Nesović, M.; Manojlović, D.; Djordjević, P.; Mićić, J.
Abstract : Chronic pulsatile subcutaneous administration of low doses of gonadotrophin releasing hormone (GnRH) is an effective therapy for men with hypogonadotrophic hypogonadism. Hypersensitivity reactions to GnRH are rare. We wish to report hypersensitivity reactions with intravenous GnRH after low dose subcutaneous pulsatile GnRH treatment in two men with hypogonadotrophic hypogonadism due to suprasellar disease.